1995
DOI: 10.1111/j.1365-2915.1995.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression and feeding success of Ixodes ricinus nymphs on BALB/c mice

Abstract: The effect of repeated infestations of Ixodes ricinus (L.) nymphs on BALB/c mice was studied. Four successive infectations resulted in an increase of tick feeding success. Tick yield and mean engorged weight increased and the length of the feeding period was reduced significantly (P < 0.05-0.01). The increase of specific anti-tick antibodies was not significant (P > 0.05). The blastogenic response of spleen lymphocytes to T-cell mitogens (Con A and PHA-P) was unimpaired or slightly enhanced, whereas the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…In contrast to lymph node cells, splenocytes from the same mice showed no signiÞcant change in proliferative responses when compared with uninfested control animals (Ferreira and Silva 1999). The Con A-stimulated proliferative response of spleen lymphocytes from BALB/c mice repeatedly infested with I. ricinus was unchanged after the primary and secondary infestations, and then increased above those from noninfested mice after the third and fourth infestations (Dusbabek et al 1995). In contrast, B-cell responses to LPS and pokeweed mitogen were suppressed after each of four infestations (Dusbabek et al 1995).…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…In contrast to lymph node cells, splenocytes from the same mice showed no signiÞcant change in proliferative responses when compared with uninfested control animals (Ferreira and Silva 1999). The Con A-stimulated proliferative response of spleen lymphocytes from BALB/c mice repeatedly infested with I. ricinus was unchanged after the primary and secondary infestations, and then increased above those from noninfested mice after the third and fourth infestations (Dusbabek et al 1995). In contrast, B-cell responses to LPS and pokeweed mitogen were suppressed after each of four infestations (Dusbabek et al 1995).…”
Section: Discussioncontrasting
confidence: 47%
“…Dermacentor andersoni salivary gland extracts contain molecules that suppress Con A-stimulated proliferation of lymphocytes from normal BALB/c mice (Bergman et al 1995(Bergman et al , 1998 and whole tick extracts of I. ricinus signiÞcantly inßuence the in vitro proliferative responses of lymphocytes from normal or previously infested laboratory mice (Borsky et al 1994, Dusbabek et al 1995. Additionally, saliva from I. dammini (ϭI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Wikel et al [25] reported that the host immune response to repeated tick feeding could possibly neutralize immunosuppressive molecules introduced by the tick. On the other hand, findings that the suppressive effect of repeated tick infestation was greater than those of the first infestation, were also reported [4,5,20]. Tick saliva also contains soluble antigens which can trigger a T lymphocyte specific response in BALB/c mice infested with ticks [12].…”
mentioning
confidence: 85%
“…Reduced proliferation was observed for the spleen cells isolated after the ® rst and third infestations but the splenocytes obtained after the second exposure to nymphs showed higher levels of reactivity to Con A than those obtained from the tick-naive controls. The in-vitro proliferative responses of splenic T-and B-lymphocyte were assessed for BALB/c mice given four sequential infestations with I. ricinus nymphs (Dusbabek et al, 1995). When compared with the corresponding cells from normal controls, the cells from the infested mice reacted similarly or with slightly enhanced reactivity to Con A or PHA.…”
Section: Host Immune Modulation By Ticksmentioning
confidence: 99%